PEMANFAATAN ULANG PELEPAH KELAPA SAWIT (Elaeis guineensis) UNTUK APLIKASI BIOMEDIS MELALUI UJI IN VITRO ANTIBAKTERI, ANTIBIOFILM, DAN ANTIOKSIDAN - Deni Setiawan; Samsul Hadi; Nurul Mardiati; Nashrul Wathan; Hilma Aulia; Siti Najwa; Muhammad Rasyid Ridha; Moch. Saiful Bachri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Elaeis guineensis fronds possess significant pharmacological potential, especially as antibiofilm and antioxidant. Previous studies have shown that E. guineensis contains flavonoids, alkaloids, tannins, and steroids that function as antioxidants. This study aims to examine the pharmacological activity of E. guineensis fronds and their antibiofilm potential. Palm fronds were macerated with aceton for 5 days. Antibacterial evaluation was conducted on four types of bacteria, and antibiofilm assessment was performed on S. aureus and E. coli. Evaluation of E. guineensis extract antioxidant activity was carried out using antioxidant tests (DPPH, FRAP, ABTS). The results of the antibacterial test showed good activity against P. acnes bacteria. The results of the antibiofilm evaluation showed significant and concentration-dependent inhibitory activity at a concentration of 1%, especially in the mid-phase for S. aureus and the maturation phase for E. coli. However, effectiveness decreased in the eradication phase. The antioxidant test showed a value of 63.93 ppm in the ABTS test. E. guineensis extract has shown strong potential as an antibacterial against P. acnes and has potential as an antibiofilm and antioxidant.